Antibacterial and cellular behavior of PLA-based bacitracin and zataria multiflora nanofibers produced by electrospinning method - Ciftci, Fatih; Duygulu, Nilufer; Yilmazer, Yasemin; Gunduz, Oguzhan; Ustundag, Cem Bulent (TAYLOR & FRANCIS LTD, 2023)
In this study, poly(lactic-acid) (PLA) polymer-based nanofiber (NF) was obtained by the electrospinning method. Antioxidant Zataria Multiflora (ZM, essential oil extract) and antibiotic effective bacitracin (BAC) materials were added to 8% PLA. ZM essential oil was extracted with Rotary and antioxidant components were investigated using GC-MS. While carvacrol constitutes 50% as the main component of ZM, it was seen as 48.06% carvacrol and 25.47% thymol as a content area. It was analyzed that ZM has a total antioxidant rate of 99.87% with 20 components. In antibacterial tests, PLA/BAC/ZM NF showed the best inhibition growth on all microorganisms (Escherichia coli, Staphylococcus aureus, Bacillus cereus, Staphylococcus epidermidis, Bacillus subtilis). In cell XTT cytotoxicity tests, it was observed that the PLA/BAC/ZM NF used in adhesion and 4 ',6-diamidino-2-phenylindole (DAPI) results showed very good adhesion to cells.
Keywords: Antioxidant; carvacrol; drug; electrospinning; essential oil; polymer nanofiber; thymol; IN-VITRO; EXTRACT; GROWTH; BOISS.; Materials Science; Polymer Science